Collagen-chitosan-hydroxyapatite composite scaffolds for bone repair in ovariectomized rats - Erivelto Luís Chacon; Mirella Romanelli Vicente Bertolo; Ana Maria de Guzzi Plepis; Virginia da Conceição Amaro Martins; Geovane Ribeiro dos Santos; Clovis Antônio Lopes Pinto; André Antônio Pelegrine; Marcelo Lucchesi Teixeira; Daniela Vieira Buchaim; Fabricio Montenegro Nazari; Rogerio Leone Buchaim; Gustavo Tenório Sugano; et al. (Scientific Reports, 2023)
Abstract Lesions with bone loss may require autologous grafts, which are considered the gold standard; however, natural or synthetic biomaterials are alternatives that can be used in clinical situations that require support for bone neoformation. Collagen and hydroxyapatite have been used for bone repair based on the concept of biomimetics, which can be combined with chitosan, forming a scaffold for cell adhesion and growth. However, osteoporosis caused by gonadal hormone deficiency can thus compromise the expected results of the osseointegration of scaffolds. The aim of this study was to investigate the osteoregenerative capacity of collagen (Co)/chitosan (Ch)/hydroxyapatite (Ha) scaffolds in rats with hormone deficiency caused by experimental bilateral ovariectomy. Forty-two rats were divided into non-ovariectomized (NO) and ovariectomized (O) groups, divided into three subgroups: control (empty defect) and two subgroups receiving collagen/chitosan/hydroxyapatite scaffolds prepared using different methods of hydroxyapatite incorporation, in situ (CoChHa1) and ex situ (CoChHa2). The defect areas were submitted to macroscopic, radiological, and histomorphometric analysis. No inflammatory processes were found in the tibial defect area that would indicate immune rejection of the scaffolds, thus confirming the biocompatibility of the biomaterials. Bone formation starting from the margins of the bone defect were observed in all rats, with a greater volume in the NO groups, particularly the group receiving CoChHa2. Less bone formation was found in the O subgroups when compared to the NO. In conclusion, collagen/chitosan/hydroxyapatite scaffolds stimulate bone growth in vivo but abnormal conditions of bone fragility caused by gonadal hormone deficiency may have delayed the bone repair process.